Desain Primer Secara In Silico untuk Amplifikasi Mutagenesis GLY349→GLU349 pada Gen Glikoprotein Virus Rabies Strain GD-SH-01 sebagai Kandidat Marker Attenuasi - Devi, Ni Wayan Antika Sri; Yowani, Sagung Chandra (Universitas Pahlawan Tuanku Tambusai, 2025)
Rabies is a fatal zoonotic disease caused by the rabies virus (RABV) with a case mortality rate almost 100% after the onset of symptoms. The Gly349→Glu349 mutation in the glycoprotein gene (G gene) of the rabies virus strain GD-SH-01 has been identified as a potential molecular marker for attenuation in the development of live attenuated vaccines. This study aims to design in silico primer pairs specific to the Gly349→Glu349 mutation to enable amplification of the target segment using Polymerase Chain Reaction (PCR). Primer design was carried out using the Primer3Plus software with parameters of primer length between 18–28 bases, melting temperature (Tm) of 55–65 °C, and GC content of 40–60%. Candidate primers were evaluated based on thermodynamic properties and secondary structure formation, and their specificity was analyzed using PrimerBLAST based on the mutated sequence. Five candidate primer pairs were generated, among which the third pair was selected as the best, producing a 175 bp PCR product with the Gly349→Glu349 mutation located at the center of the amplicon and demonstrating high specificity to the target sequence. The designed in silico primer pair shows strong potential for specific amplification of the Gly349→Glu349 mutation in the rabies virus glycoprotein gene. This design provides a scientific foundation for further molecular studies and the development of genetic analysis methods and rabies vaccines based on genetic engineering technology.